Heat and radiation resistances of diamond semiconductor in gamma-ray detection. (24th September 2019) - Ueno, Katsunori; Tadokoro, Takahiro; Ueno, Yuichiro; Sasaki, Keisuke; Koizumi, Satoshi; Chayahara, Akiyoshi; Mokuno, Yoshiaki; Hirano, Shintaro; Kaneko, Junichi H.
Abstract: We have developed a gamma-ray detector based on a single-crystal diamond in order to improve the heat and radiation resistances of gamma-ray monitors. We fabricated prototypes with two types of diamond grown by a chemical vapor deposition method. The count rates with temperature and accumulated dose were obtained using a 137 Cs gamma-ray source, then the errors at full scale (%FS) were evaluated using a method to reduce the dark count. The prototype-A worked to 643 K within 2.9%FS and to 3.1 MGy within 4.9%FS; on the other hand, the prototype-B worked to 545 K within 3.4%FS and to 5.0 MGy within 0.47%FS. This study demonstrates that the diamond semiconductor was promising for monitoring with enhanced heat and radiation resistances.